External Debt and FDI in Kosovo, Stimulating Growth - Kida, Nakije Miftar (European Journal of Economics and Business Studies, 2017)
My work is based on statistical analysis of annual data for GDP, FDI, Infrastructure and External Debt for Kosovo. They show that there was a delay in GDP growth by inappropriate trajectory configuration of positive and negative increase or decrease of economic components, some of which are included in the analysis, FDI, Infrastructure and External Debt. FDI has a positive reflection on GDP growth but it presents no statistical significance. Even the CBK statistics for FDI inflows in Kosovo show the lowest level especially after 2007, with minor improvements these last two years. While, considered as an important factor in the GDP growth, Infrastructure is represented by cellular telephone lines which cover 98 percent of the territory of Kosovo. Our empirical results suggest that external debt has had a negative impact on economic growth even though the coefficient is low, the evidence shows that the external debt is increasing and this has important implications for the economy and public policies in Kosovo.